2016
DOI: 10.1128/jcm.00818-16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostic Testing for Aspergillus

Abstract: The direct detection of Aspergillus nucleic acid in clinical specimens has the potential to improve the diagnosis of aspergillosis by offering more rapid and sensitive identification of invasive infections than is possible with traditional techniques, such as culture or histopathology. Molecular tests for Aspergillus have been limited historically by lack of standardization and variable sensitivities and specificities. Recent efforts have been directed at addressing these limitations and optimizing assay perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
0
22
1
Order By: Relevance
“…Timely and accurate diagnosis and early initiation of appropriate antifungal treatment significantly improve disease prognosis [93]. Diagnosis of invasive pulmonary aspergillosis is traditionally based on the isolation of fungi of the genus Aspergillus in culture in combination with CME or radiographic findings [95]. However, the sensitivity of culture is low and may take a long time to results.…”
Section: Molecular Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%
See 4 more Smart Citations
“…Timely and accurate diagnosis and early initiation of appropriate antifungal treatment significantly improve disease prognosis [93]. Diagnosis of invasive pulmonary aspergillosis is traditionally based on the isolation of fungi of the genus Aspergillus in culture in combination with CME or radiographic findings [95]. However, the sensitivity of culture is low and may take a long time to results.…”
Section: Molecular Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%
“…On the other hand, ME, as inexpensive and easy-to-perform complementary diagnostic method, improves positive predictive value by confirming positive culture results and provides information about the infecting cell morphology, the state of infected tissues, and biofilm formation, but is not organism specific [41]. Immuno assays which are based on the detection of fungal cell wall biomarkers, such as BDG or Aspergillus GM, have significantly reduced turn-around times compared with ME, but it has been shown that they can be low sensitive and specific in certain patient groups [95].…”
Section: Molecular Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%
See 3 more Smart Citations